FEAR MANAGEMENT OF FLOOD - Seto Mulyadi (Jurnal Psikologi, 2009)
This research is intended to identify the management of fear toward flood of eachresidence and compare fear management of flood between 2 residences. Since fear ismental state, which can be explored by questioning the object, questionnaire is used asresearch instrument. Questionnaire was developed to measure fear management, sothat fear management is categorized as latent variable. Therefore, SEM is used toanalyze data. Result show that from the view of flood fear, there is different betweenhabitants in Kampung Melayu and Kelapa Gading. Habitants in Kampung Melayushown the more risk flood experience than them in Kelapa Gading. As well, it can befound also the different between habitants in the two areas based on fear of floodmanagement. It can be also stated that habitants in Kelapa Gading have bettermanaging the risk of flooding in long term than in Kampung Melayu; whereas habitantsin Kampung Melayu manage the risk of flooding in short term. This result can be usefulinformation to government in order to manage the relocation on the time needed.